(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2022)
The notion of weaving was recently proposed to simulate a question in distributed signal processing and wireless sensor networks. In this paper we introduced the notion of a woven g-fusion frame in Hilbert C^*-modules, also we gives some properties. Finallly we study perturbation of weaving g-fusion frames.